Pengembangan Life Skill, Literasi Farmasi, dan Bilingualisme Anak Melalui Program KKN di Desa Legok Kidul, Kecamatan Paseh, Kabupaten Sumedang: Pengabdian - Mochammad Saldewa Dzulhyan; Anggi Angreani; Syifa Lailya Wigaswanda; Dinanda Periska; Kayla Aurellya; Mohammad Akhtar Fakhri Adjie; Muhammad Fahmi Siddiq Afif; Mutiara Handayani; Naufal Eka Bhuwana Herawanto; Rioni Sabila Nurfarida Hermanto; Risma Ardiati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community Service Program (KKN) is an implementation of the Tri Dharma of Higher Education in the field of community engagement. The 38th group of Universitas Muhammadiyah Bandung conducted KKN activities in Legok Kidul Village, Paseh District, Sumedang Regency, focusing on the development of children’s lifeskills, pharmaceutical literacy, and bilingualism. The program was carried out on August 12–14, 2025, at SD Talun, along with continuous learning activities at the KKN post. The method used was a participatory approach through counseling, simulation, practice, and guided learning. The results showed an improvement in children’s ability to organize daily schedules, manage simple finances, recognize drug types and logos, and practice preparing powdered medicines. In addition, routine tutoring enhanced children’s language skills, particularly in mastering basic English vocabulary through reading, singing, and simple exercises. Documentation such as photos, worksheets, and children’s outputs indicated high levels of active participation. These findings align with literature emphasizing the importance of early development of life skills, health literacy, and bilingual abilities.